Pendampingan Mendidik Siswa dengan Mutu dan Kualitas Setara dengan Sekolah Formal - Hasirah Hasirah; Wulan Wulan; Nadiyah Nadiyah; Syarifudin Syarifudin; Hasnawati Hasnawati; M. Ridhwan (STAI Auliaurrasyidin Tembilahan, 2021)
Non-Formal Education is an alternative solution. In this study, a school data management information system was built consisting of five levels of users, namely the main administrator, school administrator, teachers, students, and community. The data were in the form of school data, facilities, managers, teachers, students, and general information. In addition, there was a Learning Program Unit (SAP) which informed the materials that must be delivered in the learning process. This information system was equipped with a learning application for the National Examination for students, consisting of subject material and practice of multiple-choice questions for economics, sociology, Indonesian, English, Geography, and Mathematics. The data constructed from the Education Office of Muaro Jambi Regency and the organizers of the package C program. While the learning application materials came from certain high school textbooks.